ASSOCIATION BETWEEN SLEEP DISORDERS AND CHRONIC DISEASES IN PATIENTS OF THE BRAZILIAN NATIONAL HEALTH SYSTEM - Morais, Luana Carolina De [UNESP]; Zanuto, Everton Alex Carvalho [UNESP]; Queiroz, Dayane Cristina [UNESP]; Araújo, Monique Yndawe Castanho [UNESP]; Rocha, Ana Paula Rodrigues [UNESP]; Codogno, Jamile Sanches [UNESP] (Universidade Estadual de Maringá, 2017)
Many factors are associated with sleep disorders, causing an increase in health spending. The objective of this study was to analyze the association of sleep disorders and non-communicablechronic diseases in patients over 50 years of age, attended by Basic Health Care Units of Presidente Prudente. In total, 363 patients participated. The history of diseases was self-reported through the use of a questionnaire, the level of physical activity was evaluated by the Baecke questionnaire, and sleep quality was assessed using the Mini-Sleep Questionnaire. Anthropometric and body composition data were collected using a stadiometer and scale; patients in the highest (75th) percentile were considered obese. Statistical analysis was performed using the Student t test, chi-square test, and binary logistic regression. The results showed that sleep disorders are associated with osteoporosis, arthritis/osteoarthritis, low back pain, depression, and obesity. Additionally, obesity and physical inactivity influence the occurrence of non-communicable chronic diseases.

Inúmeros fatores estão associados aos distúrbios do sono ocasionando o aumento nos gastos com saúde. O objetivo do trabalho foi analisar a associação dos distúrbios do sono e doenças crônicas não transmissíveis em pacientes com idade superior a 50 anos atendidos por Unidades Básicas de Saúde de Presidente Prudente. Participaram 363 pacientes. O histórico de doenças foi auto relatada a partir da aplicação de questionário, o nível de atividade física foi verificado através do questionário de Baecke, e a qualidade do sono foi avaliada utilizando o Mini-Sleep questionnaire. Dados antropométricos e de composição corporal foram coletados utilizando estadiômetro e balança, foram considerados obesos os pacientes dentro do percentil 75. A análise estatística foi composta pelos testes t de Student, qui-quadrado, e regressão logística binária. Os resultados mostraram que o distúrbio do sono está associado as doenças osteoporose, artrite/artrose, dor lombar, depressão e obesidade. Adicionalmente obesidade e inatividade física influenciam na ocorrência de doenças crônicas não transmissíveis.
ASSOCIAÇÃO ENTRE DISTÚRBIOS DO SONO E DOENÇAS CRÔNICAS EM PACIENTES DO SISTEMA ÚNICO DE SAÚDE
Keywords: Sleep disturbance; Chronic diseases; Brazilian national health system.; Distúrbio do sono; Doenças crônicas; Sistema único de saúde.